Respiratory viral infections in athletes: many unanswered questions - Ruuskanen, O.; Luoto, R.; Valtonen, M.; Heinonen, O. J.; Waris, M. (Sports Medicine, 2022)
Upper respiratory tract infections ("common cold") are the most common acute illnesses in elite athletes. Numerous studies on exercise immunology have proposed that intense exercise may increase susceptibility to respiratory infections. Virological data to support that view are sparse, and several fundamental questions remain. Immunity to respiratory viral infections is highly complex, and there is a lack of evidence that minor short- or long-term alterations in immunity in elite athletes have clinical implications. The degree to which athletes are infected by respiratory viruses is unclear. During major sport events, athletes are at an increased risk of symptomatic infections caused by the same viruses as those in the general population. The symptoms are usually mild and self-limiting. It is anecdotally known that athletes commonly exercise and compete while having a respiratory viral infection; there are no virological studies to suggest that such activity would affect either the illness or the performance. The risk of myocarditis exists. Which simple mitigation procedures are crucial for effective control of seasonal respiratory viral infections is not known.